Determination of phthalates in fish fillets by liquid chromatography tandem mass spectrometry (LC-MS/MS): A comparison of direct immersion solid phase microextraction (SPME) versus ultrasonic assisted solvent extraction (UASE). (September 2020) - Panio, Antonella; Fabbri Corsarini, Stefano; Bruno, Antonia; Lasagni, Marina; Labra, Massimo; Saliu, Francesco
Abstract: Due to the increasing presence of plastic and plastic associated contaminants in the aquatic environments, the monitoring of this contamination in fish products and the understanding of possible human health implications is considered urgent. However, data are still relatively scarce, mostly due to the methodological challenges in the chemical analysis: these contaminants are ubiquitous and procedural contamination from the laboratory is frequent. In this work, we compared solid-phase microextraction (SPME) to ultrasonic assisted solvent extraction (UASE) as sample preparation methods for the liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) determination of phthalates in fish fillets. UASE was carried out with an acetone-hexane (1:1) solution and according to a reference procedure aimed to obtain the exhaustive extraction of the target analytes. SPME was carried out by applying C18 fibers in direct immersion mode and by using water/methanol 20:80 mixture to desorb the aliquot required for the analysis. Overall, SPME displayed an improved control of the background contamination and enabled lower LOQs. Precision, calculated as relative standard deviation (RSD) on replicates of a reference sample, was below 24% for both the method. Analysis of real samples purchased from Italian supermarkets showed that SPME might be an efficient tool for estimating the risk associated with fish consumption. Highlights: Chemical analysis may highlight the role of fish consumption in determining the human exposure to phthalates. A comparison between SPME and UASE in the extraction of phthalates from fish fillet was carried out. LC-MS/MS analysis showed similar matrix effect and LODs for both the methods. A satisfactory control of the background contamination was achieved only by SPME.